Optimization model for distributed energy trading based on a market value allocation mechanism in the electricity spot market - Hu, Baohua; Ding, Sheng; Xu, Zhaoyang; Cheng, Xueting; Zhu, Liangliang; Bao, Yueshuang; Wang, Kui (Frontiers in Energy Research, 2024)
As distributed energy resources become increasingly prevalent, optimizing allocation and market transactions is crucial for improving energy efficiency and economic benefits. This paper proposes a distributed energy trading market model based on a value distribution mechanism.The model establishes a direct load management approach through an electricity aggregator agent, simplifying market transaction processes and reducing transaction costs. Using a Nash bargaining model, a value distribution mechanism is designed to incentivize market participation and enhance overall system benefits. The proposed model and mechanism incorporate stochastic programming to account for uncertainties in real-time load and distributed energy output. Case studies validate the effectiveness of the proposed model and mechanism. Results demonstrate that the market model can improve the utilization of distributed resources, while the value distribution mechanism ensures fair benefit allocation among market participants. The study provides insights into the design of efficient and equitable distributed energy markets, contributing to the development of more sustainable and flexible energy systems.